2014
DOI: 10.1136/bmjqs-2013-002627
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of diagnostic errors in outpatient care: estimations from three large observational studies involving US adult populations

Abstract: BackgroundThe frequency of outpatient diagnostic errors is challenging to determine due to varying error definitions and the need to review data across multiple providers and care settings over time. We estimated the frequency of diagnostic errors in the US adult population by synthesising data from three previous studies of clinic-based populations that used conceptually similar definitions of diagnostic error.MethodsData sources included two previous studies that used electronic triggers, or algorithms, to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
344
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 514 publications
(359 citation statements)
references
References 23 publications
3
344
1
11
Order By: Relevance
“…Although diagnostic errors -including missed, incorrect, or delayed diagnoses -are common [12] and can be devastating and costly for patients [13], they have received relatively little attention and study from the patient safety community [15,[29][30][31]. The rapid pace and short duration of observation may make patients in EDs particularly vulnerable to diagnostic error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although diagnostic errors -including missed, incorrect, or delayed diagnoses -are common [12] and can be devastating and costly for patients [13], they have received relatively little attention and study from the patient safety community [15,[29][30][31]. The rapid pace and short duration of observation may make patients in EDs particularly vulnerable to diagnostic error.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients hospitalized with AMI after a treat-andrelease ED visit likely represent missed opportunities for correct diagnosis and treatment [12]. Although the effects of missed AMI diagnoses are not completely understood, some studies have found a nearly two-fold increase in the risk of death [7].…”
Section: Introductionmentioning
confidence: 99%
“…As with prior studies [11,14], the range of missed diagnoses was wide, containing both common and rare diagnoses. Unlike prior studies performed within a primary care setting the incidence of missed diagnoses within our targeted case series was relatively low, with only 2.7% of cases positive, as compared to an average population rate of 5.08% in a summative series combining several studies looking at outpatients [19]. Moreover, trials employing similar algorithms to enrich diagnostic errors found rates ranging 5.4-20.4% [11,12].…”
Section: Discussionmentioning
confidence: 70%
“…Estimates based on these and other studies suggest that most adults will experience at least one diagnostic error in their lifetimes, sometimes with devastating consequences [2]. Although correct treatment presumes a correct diagnosis, the report noted "federal resources devoted to diagnostic research are vastly eclipsed by those devoted to treatment" [1].…”
Section: Introductionmentioning
confidence: 99%